Răspuns :
(1-i)^2=1-2i-1=-2i
(1-i)^4=(-2i)(-2i)=-4
(1-i)^6=(-4)(-2i)=8i
(1-i)^7=(8i)(1-i)=8i+8
(1-i)^4=(-2i)(-2i)=-4
(1-i)^6=(-4)(-2i)=8i
(1-i)^7=(8i)(1-i)=8i+8
^ = putere
* = inmultire
(1-i)^7 = (1-i)^2*(1-i)^2*(1-i)^2*(1-i)^1
(1-i)^2= 1^2-2*1*i+i^2 ( i^2 = -1)
= 1-2i-1
= -2i
La fel facem si cu celelalte doua " (1-i)^2*(1-i)^2 "
Iar dupa ce le-am rezolvat scriem:
(1-i)^7= -2i*-2i*-2i*(1-i)
= -2i*-2i*-2i+1
= -8i^3+1
= 8i+1
Sper ca te-am ajutat. ☺
* = inmultire
(1-i)^7 = (1-i)^2*(1-i)^2*(1-i)^2*(1-i)^1
(1-i)^2= 1^2-2*1*i+i^2 ( i^2 = -1)
= 1-2i-1
= -2i
La fel facem si cu celelalte doua " (1-i)^2*(1-i)^2 "
Iar dupa ce le-am rezolvat scriem:
(1-i)^7= -2i*-2i*-2i*(1-i)
= -2i*-2i*-2i+1
= -8i^3+1
= 8i+1
Sper ca te-am ajutat. ☺